2011
DOI: 10.1021/jp207140g
|View full text |Cite
|
Sign up to set email alerts
|

Grain Growth Kinetics of ZnO:Al Nanocrystalline Powders During Calcination from Sol–Gels

Abstract: The grain growth kinetics of Al-doped ZnO nanocrystalline powders have been studied using in situ, real-time synchrotron X-ray diffraction measurements during calcination at various temperatures (400–800 °C) from sol–gels with varying levels of Al dopant (0–4 mol %). Development of the crystallite size versus time was described using a relaxation model. A grain growth activation energy of 24 ± 3 kJ/mol was obtained for undoped ZnO, while for all of the Al-doped ZnO experiments the activation energy was 43 ± 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 24 publications
5
15
0
Order By: Relevance
“…2that the lattice microstrain increases with Al concentration indicating that Al is incorporated into the ZnO lattice. The findings are in agreement with previous studies 17,18. shows the STEM micrograph of undoped ZnO nanopowders, which consists of nearly spherical crystalline particles with a small degree of agglomeration and a mean diameter of 15 nm substantiating the XRD data.The XRD patterns of undoped and 8% Al-doped pellets sintered at 900°C are shown inFig.…”
supporting
confidence: 93%
“…2that the lattice microstrain increases with Al concentration indicating that Al is incorporated into the ZnO lattice. The findings are in agreement with previous studies 17,18. shows the STEM micrograph of undoped ZnO nanopowders, which consists of nearly spherical crystalline particles with a small degree of agglomeration and a mean diameter of 15 nm substantiating the XRD data.The XRD patterns of undoped and 8% Al-doped pellets sintered at 900°C are shown inFig.…”
supporting
confidence: 93%
“…In a similar case, B. Ingham et al reported that metallic Al atoms at grain boundaries restrict ZnO grain growth in the formation of spinel crystallites as ZnAl2O3. 44 Our AFM and XPS results showed a mean grain size that was inversely proportional to the amount of metallic Be on all film surfaces. Furthermore, one can expect that increasing Be content in the films contributed to increasing the volume fraction of Be particles at grain boundaries and thus a decrease in grain size.…”
Section:  Results and Discussionmentioning
confidence: 64%
“…There are several mechanisms proposed to explain the inhibition of the ZnO crystallites growth by the presence of impurities. [23][24][25] The reduced diffusivity in ZnO due to Zn concentration decrease in the doped samples suppresses the grain growth. Also, the presence of impurities produces a retarding force on the grain boundaries, impeding the grain growth.…”
Section: Xrd Resultsmentioning
confidence: 99%
“…Moreover, in Al doped ZnO the grain growth activation energy was determined to increase in the presence of impurities. 24 All these would contribute to a gradual decrease of the grain size with the increase of the impurities concentration.…”
Section: Xrd Resultsmentioning
confidence: 99%